Association between early metabolic acidosis and bronchopulmonary dysplasia/death in preterm infants born at less than 28 weeks' gestation: an observational cohort study - Laura Notz; Mark Adams; Dirk Bassler; Vinzenz Boos (BMC, 2024)
Abstract Background Metabolic acidosis occurs frequently during the first postnatal days in extremely preterm infants and is mainly attributed to renal immaturity. Recent studies suggested a link between metabolic acidosis and the development of BPD. The aim of this study was to systematically investigate the association between severe metabolic acidosis during the first two weeks of life and bronchopulmonary dysplasia (BPD) / mortality among preterm infants born before 28 weeks' gestation. Methods Monocentric observational cohort study including 1748 blood gas samples of 138 extremely preterm infants born 2020-2022. Metabolic acidosis was defined as pH < 7.2 with base excess (BE) < -10 mmol/L or standard bicarbonate (SBC) < 12 mmol/L. Primary outcome was BPD and/or death at 36 weeks postmenstrual age. Results Fifty-six (40.6%) infants had BPD/death. Metabolic acidosis occurred in 50.0% of infants with BPD/death, compared to 22.0% of BPD-free survivors (p = 0.001) during the first 14 postnatal days. Minimum pH (median 7.12 vs. 7.19, p < 0.001), BE (median -10.9 vs. -9.5 mmol/L, p = 0.005), SBC (median 14.7 vs. 16.1 mmol/L, p < 0.001) were different between the two groups. After adjusting for confounders, pH (postnatal days 2-6), BE (postnatal day 3) and SBC (postnatal days 2-4) were significantly lower in infants with BPD/death. Metabolic acidosis on postnatal days 1-7 was associated with higher odds of BPD (adjusted Odds Ratio (aOR) 3.461, 95% CI 1.325-9.042) and BPD/death (aOR 3.087, 95% CI 1.225-7.778). Conclusions Metabolic acidosis during the first week of life was associated with higher odds of BPD/death in extremely preterm infants.